Impact of Supervision and Motivation on Elementary Teacher Professionalism in Sumay, Tebo Regency - Anggraini, Ai; Novalina, Sesti; Sari, Diana; Saputra, Dedi; Hendra, Adduwet (International Journal of Education, Language, and Social Science, 2024)
School supervisors play a strategic role in enhancing school performance by providing academic and managerial coaching. This study examines the influence of school supervisors' academic supervision and teachers' work motivation on teacher professionalism. A quantitative approach with a correlational survey method was employed. The findings reveal that academic supervision by school supervisors in Sumay District, Tebo Regency, is categorized as high, indicating effective supervision practices that require further enhancement. Academic supervision positively and significantly influences teacher professionalism, accounting for 30.04% of the variance. Similarly, teacher work motivation is also high, contributing to a positive and significant influence on teacher professionalism at 46.10%. Overall, the professionalism of elementary school teachers in the district is rated as high, demonstrating good competency levels. Furthermore, the combined positive and significant influence of academic supervision and work motivation on teacher professionalism is 47.50%. These findings underscore the critical role of academic supervision and motivation in fostering teacher professionalism and highlight areas for continued improvement.